The Investigation of Adolescents’ Level of Knowledge on Reproductive Health in the Sendangsari Family Planning Village - Anggi Rahajeng; Alifia Cahya Safitri (Jurnal Pengabdian, Riset, Kreativitas, Inovasi, dan Teknologi Tepat Guna, 2025)
Adolescence is marked by the beginning of the development of reproductive organs. Knowledge about reproductive health plays a pivotal role in influencing adolescent behaviours concerning sexual and reproductive health. The local community is a vulnerable group with sexually transmitted diseases and infections due to a lack of sufficient knowledge of reproductive health. The purpose of this research is to characterize the reproductive health literacy of local adolescents and the variables that influence this literacy. This study employed a questionnaire from Module on Reproductive Health “Integrated Community-Based Child Protection (PATBM) 2017. We presented the demographic data such as age, gender, and educational level in descriptive table. Additionally, we compared the level of knowledge in reproductive health based on the questionnaire results between Mrunggi and Kroco areas. This research reveals that on average, adolescents in both areas surprisingly demonstrate good knowledge of reproductive health based on their questionnaire results. However, there is still a need for more comprehensive education efforts and easier access to reproductive health information. It can assist them in making wiser and more empowered decisions regarding their health and reproductive rights. Meanwhile, both areas are located in Sendangsari Village, classified as one of the extremely poor villages in Yogyakarta. Therefore, addressing health issues and supporting their sustainability will present significant challenges. It is necessary to enhance the quality of local human resources so that their economic growth can be optimized. In broader context, addressing reproductive health issues is not solely a matter of individual well-being; it is a strategic investment in economic development. By fostering healthier populations, local economies can enhance productivity, reduce healthcare costs, and promote social equity, ultimately leading to sustainable economic growth.